Formulation and Evaluation of Hair Tonic for Alopecia from Cow Urine - Jyoti, G. Wagh (Asian Journal of Pharmaceutics (AJP), 2023)
Alopecia since the dawn of mankind, this issue has affected all ethnicities and both sexes to varying degrees. In allopathy, the treatment of all hair problems is expensive and cannot be afforded by poor people. Herbal hair preparations are free from various side effects that of chemically synthesized, for example, Minoxidil has side effects that are local irritation, itching and burning sensations are frequent. Instead of using various formulations for different hair problems, there is a necessity to formulate one single preparation which overcomes maximum hair problems. Since ancient times, cow pee has been utilized to treat a variety of human illnesses. It is a crucial and integral component of Panchgavya Chikitsa. Materials and Methods: Crude drug samples were collected and authentified. 10–15 g methi, kept it in aloe vera for sprouting. Sprouted methi was collected in in 500ml cow urine and collected distillate. After boiling kept it for overnight standing, filter the formulation using a muslin cloth, and packed in a suitable container. Results and Discussion: The protocol study was approved by the Institute Animal Ethical Committee for animal experimentation. The study was performed gave good hair growth activity. To improve people’s health and way of life, it is important to raise public awareness of the value and variety of uses of cow urine. In this study, cow urine is used along with methi and aloe vera to formulate a hair tonic to cure the alopecia. Conclusion: Formulated hair tonic is having excellent hair growth-promoting activity, with good antifungal activity. It will act as a potent herbal alternative without any side effects.